The last action heroes : the triumphs, flops, and feuds of Hollywood's kings of carnage - De Semlyen, Nick (Crown, 2023)
"The behind-the-scenes story of the larger-than-life action stars who ruled '80s and '90s Hollywood--Arnold Schwarzenegger, Sylvester Stallone, Bruce Willis, Jackie Chan, Steven Seagal, Chuck Norris, Dolph Lundgren, and Jean-Claude Van Damme--and the beloved films that made them stars, including Die Hard, Rambo, and The Terminator. The Last Action Heroes opens in 1990, at the Cannes film festival, where Arnold Schwarzenegger and Sylvester Stallone finally forged a truce. After years of bitter behind-the scenes combat--Stallone once threw a bowl of flowers at Schwarzenegger's head; the body count in Schwarzenegger's Commando was increased to "have a bigger d*** than Rambo"--the world's biggest action stars had at last formed a friendship. In The Last Action Heroes, film journalist Nick de Semlyen charts their wild, carnage-packed journey from enmity to friendship. He also reveals the personal stories of the colorful characters who ascended in their wake, from Jean-Claude Van Damme and Steven Seagal, to Chuck Norris and Jackie Chan. But as the '80s rolled on, the era of the invincible action hero who used muscle, martial arts, or the perfect weapon to save the day started to fade. When Jurassic Park trounced Schwarzenegger's Last Action Hero in 1993, everyone knew that the glory days of these macho men--and the vision of masculinity they celebrated--were officially over. Drawing on candid interviews with the action stars themselves, plus their collaborators, friends, and foes, The Last Action Heroes is a no-holds-barred account of a period in Hollywood history when there were no limits to the heights of fame these men achieved, or to the mayhem they wrought, onscreen and off"--